ANALISIS DAMPAK KETIDAKPASTIAN KEBIJAKAN EKONOMI GLOBAL DAN DOMESTIK TERHADAP INDEKS HARGA SAHAM GABUNGAN (IHSG) DI INDONESIA TAHUN 2020-2025 - Ageng Julitasari; Tiara Nirmala (Bhinneka Multidisiplin Journal, 2026)
This study analyzes the impact of global and domestic economic policy uncertainty on the Indonesia Composite Stock Price Index (IHSG) during 2020–2025. Global Economic Policy Uncertainty (EPU), Indonesia EPU, and the Volatility Index (VIX) are used as indicators of uncertainty affecting stock market performance. This research applies a quantitative approach using the Vector Error Correction Model (VECM) to examine both short-run and long-run relationships among variables. The analysis is supported by Uncertainty-Investment Theory, Financial Contagion Theory, and Rational Expectations Theory. The results are expected to show that increases in global and domestic policy uncertainty, as well as rising market volatility, negatively affect IHSG through higher investor risk aversion, capital outflows, and declining market confidence. This study contributes to understanding the transmission of uncertainty shocks to Indonesia’s capital market and provides implications for investors and policymakers in responding to economic uncertainty.